Technology-Driven Intergenerational Physical Activity Intervention: An Instrumental Case Study - Rachel Knight (Journal of Ageing and Longevity, 2024)
Intergenerational contact offers an under-explored strategic approach to challenging age stereotypes and positively influencing health behaviors in older adults and children. It is postulated that through the application of the constructs of Contact Theory, an effective platform for change could be established. Using an instrumental case study, the experiential effects of the intergenerational contact phenomenon were pragmatically explored from the perspective of a single familial dyad (61-year-old woman; 9-year-old boy). Semi-structured interviews were conducted with each participant, both during and following engagement with a remote, 12-week, technology-driven physical activity intervention focused on using daily step counts (acquired via any activity of their choice, using physical activity trackers) to collaboratively complete virtual walk routes during the COVID-19 pandemic. Through reflexive thematic analysis and interpretation of the data in line with the study’s aim and propositions, four core themes were identified: Reciprocal Encounter; Opportunity for Reflection and Re-evaluation; Platform for Change; and COVID-19 . In addition to the perceived positive effects on targeted health outcomes (physical activity, sedentary behavior, health-related quality of life), facilitating intergenerational contact through virtual methods could also, through opportunities to nurture and build relationships, challenge age stereotypes.